STRATEGY OF ISLAMIC EDUCATION INSTITUTIONS IN DEALING WITH MORAL DEGREDATION IN THE ERA OF SOCIETY 5.0 - Masnu’ah, Syafira; Idi, Abdullah; Wigati, Indah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In this societal era, rapid technological advances impact the growth and development of the younger generation as students, both directly and indirectly. The moral degradation of youth is one of the many harmful effects of this society era. Therefore, educational institutions must have the right strategy to deal with societal developments to face the challenges of moral degradation in the colonial era. The research was conducted at the Mazro'atul Ulum Foundation, Ds. Jaya Bakti, Kec. Madang Suku I, Kab. OKU East, South Sumatra, using qualitative field research. The results of the study show that the strategy carried out by the Mazro'atul Ulum Foundation as an Islamic educational institution facing moral degradation in the social era is by using several strategies, including building a madrasa culture and actualizing it naturally so that all school members can follow the transformation of life but still adhere to Islamic teachings, build synergies with school members, the community and with student guardians to supervise and control, apply the concepts of ta'dib, tardis and ta'lim in Islamic educational institutions.